ANALISIS PENGUKURAN TANGEN DELTA PADA BAHAN ISOLASI GENERATOR - Abdul Multi; Sigit Pudji Handojo (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT An ideal insulation is equivalent to an ideal capacitor which only stores electrical energy and does not dissipate it. In fact, when a potential difference occurs in the insulation, the polar molecules in it will move and rub together continuously so that electrical energy is dissipated in the form of heat. This energy dissipation phenomenon is equivalent to that of a resistor. Measuring the quantities associated with capacitors and resistors and their tendency to change in value with an operating time unit is the best way to determine the condition of an insulation. The value of Capacitance C, Dissipation Factor (Tan δ ) and Power Factor (Cos θ) are three significant quantities to describe the condition of an insulation. These three quantities can be measured at the same time using the Schering Bridge method in an instrument test known as the Tan-δ instrument test. These three quantities when combined with other AC and DC measurements which also include testing with low, medium and high voltages (Over Voltage) will be an illustration related to the condition of the insulation whether it is still in good condition. Keywords: Schering Bridge, dissipation factor, tangent delta